1989
DOI: 10.1177/074873048900400302
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Phase Response Curves for Drug-Induced Phase Shifts

Abstract: The effectiveness of drugs active in phase-shifting the circadian rhythm of bioluminescent glow in the unicellular dinoflagellate Gonyaulax polyedra differs, depending upon the time of drug exposure (as pulses). For two drugs tested--cycloheximide and anisomycin, both inhibitors of cytosolic protein synthesis--this function, referred to as the drug phase response curve (dPRC), differs, depending upon the ambient temperature. Since dPRCs may differ at different drug concentrations, the effects observed may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Like light, the resetting response to 6-h pulses of anisomycin was similarly affected so that higher magnitude phase shifts occurred at 37°C than at 40°C. A temperature-dependent difference in phase resetting by protein synthesis inhibitors has also been reported in Gonyaulax (Broda et al, 1989;Dunlap et al, 1980). Because the magnitude of phase shifts for both light and anisomycin are reduced at 40°C, it appears unlikely that the temperature-dependent resetting effects of these two inputs to the circadian pacemaker are mediated by a common &dquo;filter mechanism&dquo; in the signaling pathways.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Like light, the resetting response to 6-h pulses of anisomycin was similarly affected so that higher magnitude phase shifts occurred at 37°C than at 40°C. A temperature-dependent difference in phase resetting by protein synthesis inhibitors has also been reported in Gonyaulax (Broda et al, 1989;Dunlap et al, 1980). Because the magnitude of phase shifts for both light and anisomycin are reduced at 40°C, it appears unlikely that the temperature-dependent resetting effects of these two inputs to the circadian pacemaker are mediated by a common &dquo;filter mechanism&dquo; in the signaling pathways.…”
Section: Discussionmentioning
confidence: 89%
“…The temperaturedependent difference in resetting magnitude indicates that there is adaptive plasticity in the circadian system response to photic stimuli. Temperature-dependent effects on phase resetting also have been observed in other organisms such as Drosophila, Neurospora, and Gonyaulax (Broda et al, 1989;Lakin-Thomas et al, 1991;Lakin-Thomas et al, 1990;Pittendrigh et al, 1991;Pittendrigh and Takamura, 1989). For example, strains of D. auria have phase response curves with different amplitudes, and the amplitude differences depend on latitude (Pittendrigh et al, 1991;Pittendrigh and Takamura, 1989).…”
Section: Discussionmentioning
confidence: 91%
“…Surprisingly, only three previous studies have reported positive results with period lengthening to translation inhibitors: anisomycin lengthened the period to 31 hr or longer in Aplysia (28), and cycloheximide lengthened period up to 36 hr in Euglena (29) and up to 33 hr in Chlamydomonas (30). Possibly, expression of circadian rhythmicity is not 4 observable with constant inhibitor treatment at higher concentrations where period lengthening occurs (16,38,55 (35,43), Neurospora (36,40,43), Gonyaulax (38,42,(45)(46)(47), Phaseolus (39), Aplysia (31,34), and hamster (33,41) and for anisomycin pulses in Gonyaulax (37,38,42,45,47), Aplysia (27,28,32,34), chick pineal (49), and hamster (33,48). On the basis of these data, it has been suggested that translation is a requirement for the circadian pacemaker mechanism (24, 27, 28, 30-32, 35, 36, 40, 43, 44, 47, 49, 50), or more specifically, that translation is a phasedependent requirement (24,28,32,35,36,40,…”
Section: Methodsmentioning
confidence: 96%
“…Studies examining phase shifts to translation inhibitors in combination with temperature changes (42,43,45,47), or to inhibitor-insensitive mutants (40), have provided evidence favoring the argument that translation is not an integral part of the clock mechanism but simply a requirement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation